Dynamic Response of a Trunk Structure Building to Multiple Transient Loadings - Tadeusz Kasprowicz; Leopold Kruszka; Ryszard Rekucki (Communications, 2003)
The paper provides information concerning the dynamic response of building structures exposed to paraseismic loadings. Dynamic loadings can arise inside buildings or can be transmitted to buildings through subsoil, causing vibrations of structures. To carry out a dynamic diagnostics of existing buildings, it is necessary to take measurements of vibration parameters directly from the investigated structure. The paper presents some examples of such investigations, as well as a comparison of the obtained results and calculations with standard dynamic characteristics of existing buildings.